Efektivitas Peran The African Commission on Human and Peoples' Rights (ACHPR) dalam Menangani Female Genital Mutilation (FGM) di Sierra Leone: FGM di Sierra Leone - Abdul Rahman; Syaiful Anam; Sirwan Yazid Bustami (The Department of International Relations Universitas Mataram, 2022)
FGM is a form of gender-based violence against women that arises as a result of gender discrimination, namely stereotypes about women who are sacred and ideal. Sierra Leone is one of the countries with the highest practice rates and still maintains the FGM. This practice is considered dangerous and need to be stop, because has so many negative impacts. AU through its commission that addresses human rights issues, ACHPR, take part in dealing with FGM. ACHPR and WLDA then made a draft of protocol to overcome the discriminations against women. The protocol draft was ratified in the AU High Court in Maputo City, which officially named The Protocol of the African Charter on Human and Peoples’ Rights of Women in Africa or the Maputo Protocol. Then, the role of ACHPR in implementing the Maputo Protocol in dealing FGM in Sierra Leone has to be analyzed. The results of this study indicate that ACHPR are able to carry out their roles, also in 2016-2020 the rates of the FGM havedecreased by 7%. So, it can be said that the roles of ACHPR are quite effective in dealing with FGM in Sierra Leone in 2016-2020.